Dynamic and socioeconomic aspects of historical floods in Central Europe - Wanner, Heinz; Beck, Christoph; Brázdil, Rudolf; Casty, Carlo; Deutsch, Mathias; Glaser, Rüdiger; Jacobeit, Jucundus; Luterbach, Jürg; Pfister, Christian; Pohl, Stefan; Sturm, Katrin; Werner, Peter C.; et al. (ERDKUNDE, 2004)
After several disastrous floods in central Europe in the 1990s and in the year 2002 the discussion has arisen whether or not these events are the result of an anthropogenic influence such as climatic and/or land use change. In the framework of the European research programme FLOODRISK historical flood events were recorded in three severity classes based on historical documents and related to reconstructed air pressure and precipitation data. A strong, low frequency (decadal scale) variability becomes apparent in the recordings of all large river systems, indicating winter periods with higher (e.g., from 1630-1700 and 1830-1880) and lower (e.g., from 1720-1780 and 1880-1930) flood frequencies. During the 20th century a clear positive trend is only visible for the Rhine area. A circulation analysis based on a long-term Atlantic-European surface air pressure data set shows that humidity transport from the Atlantic Ocean to the European continent was strengthened during flood periods. Beside the problem of the additional influence of modified land use changes, future studies have to raise the question about the role of the North Atlantic sea surface temperatures and the ocean-atmosphere coupling (including North Atlantic Oscillation) in modulating the frequency of severe floods over the continental area. Confronted with the harm and disorder of these flooding catastrophes, the European societies were eager to get specific information and quick support. Examples show that, beside the assistance of the political authorities, fund raising campaigns of the media were very successful. Finally, it becomes apparent that risk management, when consistently utilized by the political authorities, has strengthened the bonds of national unity.